Isolation and Identification of Bacteria in Community Acquired Urinary Tract Infection with Their Antibiotic Sensitivity Pattern at PMC Hospital Nawabshah - Arooj Ali, Rabail Bashir, Konain Atta, Shabana Halepoto, Qurban Ali Khaskheli, Irum Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to isolate and identify bacteria in community-acquired urinary tract infections (UTIs) and assess their antibiotic sensitivity patterns. Methodology: A cross-sectional study was conducted in the Department of Microbiology, Peoples University of Medical & Health Sciences for Women, Nawabshah, from January 2, 2023, to June 3, 2023. A total of 154 adult patients (18–60 years) with symptomatic bacteriuria were enrolled. Midstream urine samples were collected and inoculated on Cystine Lactose Electrolyte Deficient (CLED) agar, blood agar, and MacConkey agar. Bacterial identification was performed using Gram staining, colony morphology, and biochemical tests. Antibiotic susceptibility was assessed via the Kirby-Bauer disc diffusion method on Müller–Hinton agar. Results: The mean age of patients was 40.42 ± 10.57 years, and the mean BMI was 27.31 ± 3.28. The most common isolates were Escherichia coli (34.4%), Klebsiella pneumoniae (24%), Proteus mirabilis (11.7%), Staphylococcus saprophyticus (9.1%), and Pseudomonas aeruginosa (11%). Sensitivity to ampicillin was highest for E. coli (94.3%), followed by P. mirabilis (88.9%) and S. saprophyticus (92.9%). Resistance to ampicillin was notable across all isolates. Conclusion: UTIs were more common in females, with E. coli being the predominant pathogen. A high resistance pattern to commonly prescribed antibiotics was observed, emphasizing the need for cautious antibiotic use. Keywords: Antibiotic Sensitivity, Cystine Lactose Electrolyte Deficient, E. coli, MacConkey Agar, Urinary Tract Infection,